The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/eat.22621
|View full text |Cite
|
Sign up to set email alerts
|

Emotional eating and in vivo norepinephrine transporter availability in obesity: A [11C]MRB PET pilot study

Abstract: These results indicate that central in vivo NET availability is altered in EE of individuals with obesity. © 2016 Wiley Periodicals, Inc.(Int J Eat Disord 2017; 50:152-156).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…This study did not find significant differences in EE scores and regional NET levels between healthy controls and obese participants. However, for obese individuals higher EE scores correlated with lower NET availability in the locus coeruleus and higher NET availability in the left thalamus (50). Collectively, these studies suggest that NE transmission is regionally impaired in substance use disorder, obese, and EE populations (50,52).…”
Section: Pet Imaging In Obesity and Food Addictionmentioning
confidence: 72%
See 2 more Smart Citations
“…This study did not find significant differences in EE scores and regional NET levels between healthy controls and obese participants. However, for obese individuals higher EE scores correlated with lower NET availability in the locus coeruleus and higher NET availability in the left thalamus (50). Collectively, these studies suggest that NE transmission is regionally impaired in substance use disorder, obese, and EE populations (50,52).…”
Section: Pet Imaging In Obesity and Food Addictionmentioning
confidence: 72%
“…However, for obese individuals higher EE scores correlated with lower NET availability in the locus coeruleus and higher NET availability in the left thalamus (50). Collectively, these studies suggest that NE transmission is regionally impaired in substance use disorder, obese, and EE populations (50,52). These results suggest that regional fluctuations in NET availability determine the deviations in motivated behavior, such as emotional eating, which are seen in substance use disorder and obesity.…”
Section: Pet Imaging In Obesity and Food Addictionmentioning
confidence: 76%
See 1 more Smart Citation
“…Noradrenergic dysfunction and impaired NE clearance are implicated in obesity. Consequently, the researchers using 11 C-MRB PET have come to mutual conclusions that the NET availability in the thalamus region of obese adults is decreased when compared to healthy controls (Li et al 2014;Bresch et al 2017). In addition, by measuring the CNS NET availability, it is possible to predict the result of a dietary intervention, and is helpful for adjusting treatment options of highly obese adults (Vettermann et al 2018).…”
Section: C-mrbmentioning
confidence: 99%
“…Another study with the same tracer performed by Hesse and colleagues did not find significant differences people with and without obesity (Bresch et al., 2017a, Hesse et al., 2017). Interestingly, the same group found within‐obesity‐group relationships with [11C]MRB BP ND values suggestive of NET involvement in eating behaviors like emotional eating and susceptibility to hunger (Bresch et al., 2017a,b). They also suggested that NET availability might be helpful as a biomarker for predicting outcomes to dietary interventions, which could inform individualized treatment of obesity (Vettermann et al., 2018).…”
Section: Introductionmentioning
confidence: 79%